Polyolefin composition with PTC (Positive Temperature Coefficient) effect as well as preparation method and product thereof

By using hydrotalcite-coated modified carbon nanotubes and acetylene carbon black in polyolefin materials, the problems of degraded performance and poor stability of existing PTC materials are solved, and the durable PTC effect and high quality stability of the polyolefin composition are achieved.

CN119899439AActive Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311375830.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-29
Estimated Expiration
2043-10-23

AI Technical Summary

Technical Problem

The existing polyolefin/carbon black PTC materials have degraded performance due to high filling amounts, difficulty in processing, and poor quality stability, and the PTC effect is prone to attenuation or disappearance.

Method used

A polyolefin composition containing 3.0 to 6.0 parts of carbon black and 2.0 to 4.0 parts of hydrotalcite-covered modified carbon nanotubes was prepared by using hydrotalcite-covered modified carbon nanotubes.

Benefits of technology

The long-lasting PTC effect of the polyolefin composition is achieved, the strength and processing ease of the material are improved, and the quality stability of the material is enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a polyolefin composition with a PTC (Positive Temperature Coefficient) effect as well as a preparation method and a product thereof, and belongs to the technical field of macromolecular heat-sensitive materials, the composition comprises the following components in parts by weight: 100 parts of polyolefin resin, 3.0-6.0 parts of carbon black, 2.0-4.0 parts of hydrotalcite coated modified carbon nanotubes, 3.0-5.0 parts of a toughening agent, 0.3-0.4 part of an antioxidant and 0.02-0.04 part of a processing aid. According to the invention, the hydrotalcite is used for coating and modifying the carbon nanotubes and then is cooperatively used with the acetylene black, so that the produced polyethylene composition has a lasting PTC effect, and meanwhile, the composition is high in strength and easy to process and form.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer thermosensitive materials, in particular to a polyolefin composition for producing a self-limiting temperature material, a preparation method thereof and a product containing the same. Background Art

[0002] Conductive materials with PTC (Positive Temperature Coefficient) effect are one of the most rapidly developing functional polymer materials. The resistance of this material increases with the increase of temperature, and it can reduce or even cut off the current when the temperature rises. When the temperature drops, the circuit is restored to prevent overheating and overcurrent of the circuit, achieving the effect of automatic temperature control. PTC materials can be widely used in the fields of self-limiting temperature and overcurrent protection components such as petroleum and chemical fluid transportation pipelines, heating floors, and heating belts.

[0003] At present, PTC materials are mainly divided into two categories: ceramic-based and polymer-based. Polymer-based PTC materials are mainly composed of resin polymers with conductive additives added, and have the advantages of light weight, low price and easy molding. Among them, polyolefin / carbon black PTC materials are the most widely used.

[0004] Polyolefin / carbon black PTC materials use carbon black as a conductive additive. To make the material produce the PTC effect, the amount of carbon black added is usually high, generally exceeding 15% by weight. The high filling amount causes a significant decrease in the performance of the PTC material. At the same time, the system viscosity increases, making processing difficult. In addition, the high carbon black content also leads to poor quality stability of the material. After a period of use, the PTC effect will decay or even disappear. Summary of the invention

[0005] The present invention aims at the deficiencies of the prior art and provides a polyolefin composition with a durable PTC effect. The composition has excellent performance and is very easy to process and shape.

[0006] One of the objects of the present invention is to provide a polyolefin composition having a PTC effect.

[0007] A second object of the present invention is to provide a method for preparing the polyolefin composition having the PTC effect.

[0008] A third object of the present invention is to provide a product comprising the polyolefin composition having the PTC effect.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] In the first aspect, the present invention provides a polyolefin composition having a PTC effect, comprising the following components in parts by weight: 100 parts of a polyolefin resin, 3.0 to 6.0 parts of carbon black, 2.0 to 4.0 parts of hydrotalcite-coated modified carbon nanotubes, 3.0 to 5.0 parts of a toughening agent, 0.3 to 0.4 parts of an antioxidant, and 0.02 to 0.04 parts of a processing aid.

[0011] The following is a detailed description of each component:

[0012] There is no particular limitation on the source of the polyolefin resin, which can be commercially available or prepared by methods known in the art.

[0013] Preferably, the polyolefin resin may include but is not limited to polyethylene, polypropylene, poly-1-butene, ethylene-vinyl acetate copolymer, etc., preferably a high-density polyethylene (HDPE) resin; preferably, the melt flow rate of the high-density polyethylene (HDPE) resin is 10.0-15.0 g / 10 min (190° C., 21.6 kg), such as HDPE DGDB2480 of Qilu Petrochemical Company, but not limited thereto.

[0014] The amount of the polyolefin resin added was 100 parts.

[0015] The carbon black may include but is not limited to acetylene carbon black, pigment carbon black, reinforcing carbon black, etc., preferably acetylene carbon black; preferably, the acetylene carbon black has a particle size of 40 to 50 nm and an oil absorption value of 3.0 mL / g, such as the acetylene carbon black from Zhejiang Chun'an Chemical Plant, but is not limited thereto.

[0016] The amount of carbon black added is 3-6 parts, for example, 3 parts, 4 parts, 5 parts, 6 parts, but not limited thereto.

[0017] The hydrotalcite-coated modified carbon nanotubes are obtained by activation modification of carbon nanotubes (CNTs) and hydrotalcite coating.

[0018] Preferably, the hydrotalcite-coated modified carbon nanotubes are prepared by the following method:

[0019] The carbon nanotubes are placed in a strong acid solution for treatment to obtain modified carbon nanotubes, and then washed with water until the carbon nanotubes are neutrally dispersed in an aqueous phase to obtain a dispersion 1;

[0020] Dispersing hydrotalcite in water phase, adding benzoic acid to react to obtain dispersion 2;

[0021] Dispersion liquid 2 was added into dispersion liquid 1 and mixed thoroughly to obtain hydrotalcite-coated modified carbon nanotubes.

[0022] Specifically, the hydrotalcite-coated modified carbon nanotubes are prepared by the following method:

[0023] Add concentrated nitric acid (concentration of 80% to 85%) to carbon nanotubes at 10% to 15% of the weight of the carbon nanotubes, heat to 85° C. to 90° C., stir at constant temperature for 45 min to 50 min, cool to room temperature, wash with water until neutrally dispersed in the aqueous phase to obtain dispersion 1;

[0024] Add 2% to 3% of the weight of aluminum-magnesium hydrotalcite polyoxyethylene sorbitan monostearate (Tween-60) to deionized water, heat to 60° C. to 70° C., then add aluminum-magnesium hydrotalcite and disperse in the aqueous phase to form a dispersion, add 5% to 8% of benzoic acid by weight of the aluminum-magnesium hydrotalcite, react for 30 minutes, add sodium hydroxide to adjust the pH value to 7.5 to 8.0, cool to room temperature, and obtain dispersion 2;

[0025] Dispersion 2 (solid content is 8% to 10% of the solid content of dispersion 1) is added dropwise to dispersion 1, stirred for 10 minutes, centrifuged and dehydrated, and dried at 130° C. to 140° C. to obtain hydrotalcite-coated modified carbon nanotubes.

[0026] The added amount of the hydrotalcite-coated modified carbon nanotubes is 2-4 parts, for example, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, but not limited thereto.

[0027] The toughening agent may be a toughening resin known in the art, including but not limited to POE, EVA, and PU.

[0028] Preferably, the toughening agent is POE resin with a Shore A hardness of 52 ~ 60, such as a Shore A hardness of 54, such as POE ENGAGE 8842 from The Dow Chemical Company, but not limited thereto.

[0029] The amount of the toughening agent added is 3-5 parts, for example, 3 parts, 4 parts, 5 parts, but not limited thereto.

[0030] The antioxidant may be any antioxidant known in the art, including but not limited to hindered phenol antioxidants and hindered amine antioxidants.

[0031] Preferably, the antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, such as the antioxidant Irganox 1010 produced by BASF, but is not limited thereto.

[0032] The added amount of the antioxidant is 0.3-0.4 parts, for example, 0.3 parts, 0.32 parts, 0.35 parts, 0.38 parts, 0.4 parts, but not limited thereto.

[0033] The processing aid may be any known aid in the art, including but not limited to silicone processing aids and fluorine-containing organic processing aids.

[0034] Preferably, the processing aid is a fluorine-containing aid, such as LANPOLY PPA2800 from LANPOLY Polymer Technology Co., Ltd., but not limited thereto.

[0035] The added amount of the processing aid is 0.02-0.04 parts, for example, it can be 0.02 parts, 0.03 parts, 0.04 parts, but it is not limited thereto.

[0036] In a second aspect, the present invention provides a method for preparing a polyolefin composition having a PTC effect, comprising the following steps: kneading the polyolefin composition having a PTC effect and then molding it to obtain a special material for the polyolefin composition.

[0037] Specifically, the preparation method comprises:

[0038] Add polyolefin resin, carbon black, hydrotalcite-coated modified carbon nanotubes, toughening agent, antioxidant and processing aid into an internal mixer, mix and plasticize at 190°C for 10-12 minutes, form into sheets through a double-roll mill, and then cut into pellets through a pelletizer to form special materials.

[0039] In a third aspect, the present invention provides an article comprising a polyolefin composition having a PTC effect.

[0040] The product can be a self-limiting temperature product such as a heating belt, a heating floor, etc.

[0041] Beneficial Effects

[0042] The invention uses the etched hydrotalcite to coat and modify the carbon nanotubes and then uses them in coordination with acetylene black to produce a polyethylene composition with a lasting PTC effect. The composition has high strength and is easy to process and shape.

[0043] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.

[0045] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.

[0046] The raw materials involved in the embodiments and comparative examples are as follows:

[0047] The high-density polyethylene (HDPE) resin is HDPE DGDB2480 from Qilu Petrochemical Company, and the melt flow rate is 10.0-12.0 g / 10 min (190° C., 21.6 kg).

[0048] The carbon black was acetylene black from Chun'an Chemical Plant in Zhejiang Province, with a particle size of 40 to 50 nm and an oil absorption value of 3.0 mL / g.

[0049] The toughening agent is POE ENGAGE 8842 from Dow Chemical Company, with a Shore A hardness of 54.

[0050] The antioxidant is Irganox 1010 produced by BASF.

[0051] The processing aid is LANPOLY PPA2800 from Luju Polymer Technology Co., Ltd.

[0052] Embodiment 1:

[0053] Preparation of modified carbon nanotubes:

[0054] 1. Add 85% concentrated nitric acid (12% by weight of carbon nanotubes) to 200 g of carbon nanotubes, heat to 85° C., stir at constant temperature for 50 min, cool to room temperature, wash with water until neutral, and redisperse in water to obtain aqueous dispersion 1 (solid content 35%).

[0055] 2. Add 2.5% of polyoxyethylene sorbitan monostearate (Tween-60) by weight of aluminum-magnesium hydrotalcite to 500g of deionized water, heat to 65°C, add 100g of aluminum-magnesium hydrotalcite and disperse in the aqueous phase to form a dispersion, add 6% of benzoic acid by weight of aluminum-magnesium hydrotalcite, react for 30min, add sodium hydroxide to adjust the pH value to 7.8, cool to room temperature, and obtain dispersion 2 (solid content of 18%, with water loss).

[0056] 3. Add dispersion 2 (solid content weight is 9% of the total solid content of dispersion 1) dropwise into dispersion 1, stir thoroughly for 10 minutes, centrifuge and dehydrate, and dry at 135° C. to obtain modified carbon nanotubes.

[0057] The polyethylene composition with a long-lasting PTC effect is composed of the following components (parts by weight, the same below):

[0058] 100 parts of high-density polyethylene (HDPE) resin, 5.0 parts of carbon black, 3.0 parts of modified carbon nanotubes, 4.0 parts of toughening agent, 0.3 parts of antioxidant, and 0.02 parts of processing aid.

[0059] Preparation method of polyethylene composition with lasting PTC effect:

[0060] Add HDPE resin and various additives into an internal mixer, mix and plasticize at 190°C for 10 minutes, pass through a double-roll mill to form sheets, and then pass through a granulator to form special materials.

[0061] Performance testing method:

[0062] The special material is pressed into standard samples by a molding machine and then various performance tests are carried out.

[0063] Tensile strength and elongation at break: tested according to GB / T 1040-2008.

[0064] Volume resistivity: Tested in accordance with GB / T 1410-2006.

[0065] PTC strength: Use a DC double-arm bridge to test the resistance value of the sample at different temperatures, plot the logarithm of the resistivity against the temperature, and obtain the resistivity-temperature curve of the sample. The PTC strength is equal to the logarithm of the ratio of the maximum resistivity in the curve to its resistivity at room temperature.

[0066] Durability test: Keep the power on for 10 days and test the resistivity change.

[0067] The performance test results are shown in Table 1.

[0068] Embodiment 2:

[0069] Preparation of modified carbon nanotubes:

[0070] 1. Add 82% concentrated nitric acid (15% by weight of carbon nanotubes) to 200 g of carbon nanotubes, heat to 90° C., stir at constant temperature for 45 min, cool to room temperature, wash with water until neutral, and redisperse in water to obtain aqueous dispersion 1 (solid content 35%).

[0071] 2. Add 3.0% of polyoxyethylene sorbitan monostearate (Tween-60) by weight of aluminum-magnesium hydrotalcite to 500g of deionized water, heat to 65°C, add aluminum-magnesium hydrotalcite and disperse in the aqueous phase to form a dispersion, add 7% of benzoic acid by weight of aluminum-magnesium hydrotalcite, react for 30min, add sodium hydroxide to adjust the pH value to 8.0, cool to room temperature, and obtain dispersion 2 (solid content of 20%, with water loss).

[0072] 3. Add dispersion 2 (solid content weight is 10% of the total solid content of dispersion 1) dropwise into dispersion 1, stir thoroughly for 10 minutes, centrifuge and dehydrate, and dry at 140° C. to obtain modified carbon nanotubes.

[0073] The polyethylene composition with a long-lasting PTC effect is composed of the following components (parts by weight, the same below):

[0074] 100 parts of high-density polyethylene (HDPE) resin, 6.0 parts of carbon black, 2.0 parts of modified carbon nanotubes, 3.0 parts of toughening agent, 0.3 parts of antioxidant, and 0.04 parts of processing aid.

[0075] Preparation method of polyethylene composition with lasting PTC effect:

[0076] Add HDPE resin and various additives into an internal mixer, mix and plasticize at 190°C for 10 minutes, pass through a double-roll mill to form sheets, and then pass through a granulator to form special materials.

[0077] The performance test method is the same as in Example 1, and the performance test results are shown in Table 1.

[0078] Embodiment 3:

[0079] Preparation of modified carbon nanotubes:

[0080] 1. Add 80% concentrated nitric acid (10% by weight of carbon nanotubes) to 200 g of carbon nanotubes, heat to 85° C., stir at constant temperature for 45 min, cool to room temperature, wash with water until neutral, and redisperse in water to obtain aqueous dispersion 1 (solid content 35%).

[0081] 2. Add 2.0% of polyoxyethylene sorbitan monostearate (Tween-60) by weight of aluminum-magnesium hydrotalcite to deionized water, heat to 60°C, add aluminum-magnesium hydrotalcite and disperse in the aqueous phase to form a dispersion, add 6% of benzoic acid by weight of aluminum-magnesium hydrotalcite, react for 30 minutes, add sodium hydroxide to adjust the pH value to 7.5, cool to room temperature, and obtain dispersion 2 (solid content of 18%, with water loss).

[0082] 3. Add dispersion 2 (solid content weight is 8% of the total solid content of dispersion 1) dropwise into dispersion 1, stir thoroughly for 10 minutes, centrifuge and dehydrate, and dry at 130° C. to obtain modified carbon nanotubes.

[0083] The polyethylene composition with a long-lasting PTC effect is composed of the following components (parts by weight, the same below):

[0084] 100 parts of high-density polyethylene (HDPE) resin, 3.0 parts of carbon black, 4.0 parts of modified carbon nanotubes, 5.0 parts of toughening agent, 0.4 parts of antioxidant, and 0.04 parts of processing aid.

[0085] Preparation method of polyethylene composition with lasting PTC effect:

[0086] Add HDPE resin and various additives into an internal mixer, mix and plasticize at 190°C for 12 minutes, pass through a double-roll mill to form sheets, and then pass through a granulator to form special materials.

[0087] The performance test method is the same as in Example 1, and the performance test results are shown in Table 1.

[0088] Embodiment 4:

[0089] Preparation of modified carbon nanotubes:

[0090] 1. Add 85% concentrated nitric acid (13% by weight of carbon nanotubes) to 200 g of carbon nanotubes, heat to 90° C., stir at constant temperature for 48 min, cool to room temperature, wash with water until neutral, and redisperse in water to obtain aqueous dispersion 1 (solid content 35%).

[0091] 2. Add 2.5% of polyoxyethylene sorbitan monostearate (Tween-60) by weight of aluminum-magnesium hydrotalcite to deionized water, heat to 65°C, add aluminum-magnesium hydrotalcite and disperse in the aqueous phase to form a dispersion, add 5% of benzoic acid by weight of aluminum-magnesium hydrotalcite, react for 30 minutes, add sodium hydroxide to adjust the pH value to 7.5, cool to room temperature, and obtain dispersion 2 (solid content of 20%, with water loss).

[0092] 3. Add dispersion 2 (solid content weight is 9% of the total solid content of dispersion 1) dropwise into dispersion 1, stir thoroughly for 10 minutes, centrifuge and dehydrate, and dry at 130° C. to obtain modified carbon nanotubes.

[0093] The polyethylene composition with a long-lasting PTC effect is composed of the following components (parts by weight, the same below):

[0094] 100 parts of high-density polyethylene (HDPE) resin, 4.0 parts of carbon black, 3.5 parts of modified carbon nanotubes, 4.0 parts of toughening agent, 0.4 parts of antioxidant, and 0.02 parts of processing aid.

[0095] Preparation method of polyethylene composition with lasting PTC effect:

[0096] Add HDPE resin and various additives into an internal mixer, mix and plasticize at 190°C for 10 minutes, pass through a double-roll mill to form sheets, and then pass through a granulator to form special materials.

[0097] The performance test method is the same as in Example 1, and the performance test results are shown in Table 1.

[0098] Embodiment 5:

[0099] Preparation of modified carbon nanotubes:

[0100] 1. Add 82% concentrated nitric acid (14% by weight of carbon nanotubes) to 200 g of carbon nanotubes, heat to 90° C., stir at constant temperature for 46 min, cool to room temperature, wash with water until neutral, and redisperse in water to obtain aqueous dispersion 1 (solid content 35%).

[0101] 2. Add 2.0% of polyoxyethylene sorbitan monostearate (Tween-60) by weight of aluminum-magnesium hydrotalcite to deionized water, heat to 60°C, add aluminum-magnesium hydrotalcite and disperse in the aqueous phase to form a dispersion, add 6% of benzoic acid by weight of aluminum-magnesium hydrotalcite, react for 30 minutes, add sodium hydroxide to adjust the pH value to 7.7, cool to room temperature, and obtain dispersion 2 (solid content of 19%, with water loss).

[0102] 3. Add dispersion 2 (solid content weight is 10% of the total solid content of dispersion 1) dropwise into dispersion 1, stir thoroughly for 10 minutes, centrifuge and dehydrate, and dry at 135° C. to obtain modified carbon nanotubes.

[0103] The polyethylene composition with a long-lasting PTC effect is composed of the following components (parts by weight, the same below):

[0104] 100 parts of high-density polyethylene (HDPE) resin, 5.0 parts of carbon black, 2.5 parts of modified carbon nanotubes, 3.5 parts of toughening agent, 0.3 parts of antioxidant, and 0.03 parts of processing aid.

[0105] Preparation method of polyethylene composition with lasting PTC effect:

[0106] Add HDPE resin and various additives into an internal mixer, mix and plasticize at 190°C for 10 minutes, pass through a double-roll mill to form sheets, and then pass through a granulator to form special materials.

[0107] The performance test method is the same as in Example 1, and the performance test results are shown in Table 1.

[0108] Table 1 Performance test results

[0109] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Tensile strength, MPa 26.5 26.6 27.2 26.9 26.8 Elongation at break, % 684 680 704 695 695 Volume resistivity, Ω·m 850 876 838 844 862 Volume resistivity after durability test, Ω·m 854 879 842 851 867 Volume resistivity change rate after durability test, % 0.5 0.3 0.5 0.8 0.6 PTC Strength 5.2 5.5 4.9 5.1 5.3

[0110] Comparative Example 1:

[0111] Preparation of modified carbon nanotubes: same as in Example 1.

[0112] The polyethylene composition is composed of the following components (parts by weight, the same below):

[0113] 100 parts of high-density polyethylene (HDPE) resin, 8.0 parts of modified carbon nanotubes, 4.0 parts of toughening agent, 0.3 parts of antioxidant, and 0.02 parts of processing aid.

[0114] Preparation method of polyethylene composition:

[0115] Add HDPE resin and various additives into an internal mixer, mix and plasticize at 190°C for 10 minutes, pass through a double-roll mill to form sheets, and then pass through a granulator to form special materials.

[0116] The performance test method is the same as in Example 1, and the performance test results are shown in Table 2.

[0117] Comparative Example 2:

[0118] The polyethylene composition is composed of the following components (parts by weight, the same below):

[0119] 100 parts of high-density polyethylene (HDPE) resin, 5.0 parts of carbon black, 3.0 parts of carbon nanotubes, 4.0 parts of toughening agent, 0.3 parts of antioxidant, and 0.02 parts of processing aid.

[0120] Preparation method of polyethylene composition:

[0121] Add HDPE resin and various additives into an internal mixer, mix and plasticize at 190°C for 10 minutes, pass through a double-roll mill to form sheets, and then pass through a granulator to form special materials.

[0122] The performance test method is the same as in Example 1, and the performance test results are shown in Table 2.

[0123] Comparative Example 3:

[0124] The polyethylene composition is composed of the following components (parts by weight, the same below):

[0125] 100 parts of high-density polyethylene (HDPE) resin, 8.0 parts of carbon black, 4.0 parts of toughening agent, 0.3 parts of antioxidant, and 0.02 parts of processing aid.

[0126] Preparation method of polyethylene composition:

[0127] Add HDPE resin and various additives into an internal mixer, mix and plasticize at 190°C for 10 minutes, pass through a double-roll mill to form sheets, and then pass through a granulator to form special materials.

[0128] The performance test method is the same as in Example 1, and the performance test results are shown in Table 2.

[0129] Comparative Example 4:

[0130] The polyethylene composition is composed of the following components (parts by weight, the same below):

[0131] 100 parts of high-density polyethylene (HDPE) resin, 23.0 parts of carbon black, 4.0 parts of toughening agent, 0.3 parts of antioxidant, and 0.02 parts of processing aid.

[0132] Preparation method of polyethylene composition:

[0133] Add HDPE resin and various additives into an internal mixer, mix and plasticize at 190°C for 10 minutes, pass through a double-roll mill to form sheets, and then pass through a granulator to form special materials.

[0134] The performance test method is the same as in Example 1, and the performance test results are shown in Table 2.

[0135] Table 2 Performance test results

[0136] Test items Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Tensile strength, MPa 26.9 26.7 26.7 22.4 Elongation at break, % 682 684 688 490 Volume resistivity, Ω·m 286 584 <![CDATA[3.2×10 5 ]]> 1206 Volume resistivity after durability test, Ω·m - - - 1358 Volume resistivity change rate after durability test, % - - - 12.6 PTC Strength none none none 4.1

[0137] - indicates not tested.

[0138] Comparative Example 1 uses modified carbon nanotubes as conductive additives, and the other components are the same as those in Example 1; Comparative Example 2 uses unmodified carbon nanotubes and acetylene black as conductive additives, and the other components are the same as those in Example 1; Comparative Example 3 uses only acetylene black as conductive additive, and the result is that the material cannot produce PTC effect and cannot be used as PTC material. Comparative Example 4 uses 23 parts of acetylene black to produce PTC effect, and the durability of the PTC effect of the material is poor.

[0139] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.

Claims

1. A polyolefin composition having a PTC effect, characterized in that: The invention comprises the following components in parts by weight: 100 parts of polyolefin resin, 3.0-6.0 parts of carbon black, 2.0-4.0 parts of hydrotalcite-coated modified carbon nanotubes, 3.0-5.0 parts of toughening agent, 0.3-0.4 parts of antioxidant and 0.02-0.04 parts of processing aid.

2. The polyolefin composition having a PTC effect according to claim 1, characterized in that: The polyolefin resin is one or more selected from polyethylene, polypropylene, poly-1-butene and ethylene-vinyl acetate copolymer, preferably a high-density polyethylene resin; Preferably, the high-density polyethylene resin has a melt flow rate of 10.0 to 15.0 g / 10 min at 190° C. and 21.6 kg.

3. The polyolefin composition having a PTC effect according to claim 1, characterized in that: The carbon black is one or more selected from acetylene carbon black, pigment carbon black and reinforcing carbon black, preferably acetylene carbon black; Preferably, the particle size of the acetylene carbon black is 40 to 50 nm, and the oil absorption value is 2.0 to 4.0 mL / g.

4. The polyolefin composition having a PTC effect according to claim 1, characterized in that: The hydrotalcite-coated modified carbon nanotubes are prepared by the following method: The carbon nanotubes are placed in a strong acid solution for treatment to obtain modified carbon nanotubes, and then washed with water until the carbon nanotubes are neutrally dispersed in an aqueous phase to obtain a dispersion 1; Dispersing hydrotalcite in water phase, adding benzoic acid to react to obtain dispersion 2; Dispersion liquid 2 was added into dispersion liquid 1 and mixed thoroughly to obtain hydrotalcite-coated modified carbon nanotubes.

5. The polyolefin composition having a PTC effect according to claim 4, characterized in that: The hydrotalcite-coated modified carbon nanotubes are prepared by the following method: Add carbon nanotubes to concentrated nitric acid containing 10% to 15% of the weight of carbon nanotubes, heat to 85° C. to 90° C., stir at constant temperature for 45 min to 50 min, cool to room temperature, wash with water until neutrally dispersed in the aqueous phase to obtain dispersion 1; Add 2% to 3% of polyoxyethylene sorbitan monostearate by weight of aluminum-magnesium hydrotalcite to deionized water, heat to 60°C to 70°C, then add aluminum-magnesium hydrotalcite and disperse in the water phase to form a dispersion, add 5% to 8% of benzoic acid by weight of aluminum-magnesium hydrotalcite, react for 30 minutes, adjust the pH value to 7.5 to 8.0, and cool to room temperature to obtain dispersion 2; Dispersion 2 was added dropwise to dispersion 1, the solid content of dispersion 2 being 8% to 10% of the solid content of dispersion 1. After being fully stirred for 10 minutes, the dispersion was centrifuged for dehydration and dried at 130° C. to 140° C. to obtain hydrotalcite-coated modified carbon nanotubes.

6. The polyolefin composition having a PTC effect according to claim 1, characterized in that: The toughening agent is one or more selected from POE resin, EVA resin and PU resin, preferably POE resin; Preferably, the Shore A hardness of the POE resin is 52-60.

7. The polyolefin composition having a PTC effect according to claim 1, characterized in that: The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

8. The polyolefin composition having a PTC effect according to claim 1, characterized in that: The processing aid is a fluorine-containing aid.

9. A method for preparing a polyolefin composition having a PTC effect, characterized in that: The method comprises the following steps: mixing and molding the polyolefin composition with PTC effect as claimed in any one of claims 1 to 8 to obtain a special material for the polyolefin composition.

10. A product, characterized in that The article comprises the polyolefin composition having a PTC effect as described in any one of claims 1 to 8; Preferably, the article comprises a heating tape or a heated floor.

Citation Information

Patent Citations

  • Polymer-carbon nanotube-carbon black composite temperature self-regulating positive temperature coefficient (PTC) electric heating material

    CN102344598A

  • Ultralow-resistance organic positive temperature coefficient (PTC) composite material and preparation method thereof

    CN102675718A

  • Polyolefin / carbon nano tube high-conductive composite material and preparation method thereof

    CN108117684A

  • Positive temperature coefficient materials with reduced negative temperature coefficient effect

    US20110297891A1